Fire severity has lasting effects on the distribution of arboreal mammals in a resprouting forest. (16th August 2022) - Campbell‐Jones, Maggie M.; Bassett, Michelle; Bennett, Andrew F.; Chia, Evelyn K.; Leonard, Steve; Collins, Luke
Abstract: Wildfire severity is assumed to be an important driver of habitat availability and species' distributions in forest ecosystems. Many studies have focused on the immediate or short‐term effects of fire severity in fire‐prone ecosystems, with much less focus on how long the effect of fire severity may persist. We examined the effect of fire severity on the distribution of arboreal mammals at 3 and 10 years post‐fire, in a temperate forest ecosystem dominated by eucalypts that have strong resistance and resilience to low and high severity fire, respectively. The study took place within areas affected by the 2009 Kilmore East‐Murrindindi wildfires in south‐eastern Australia. Sites were established across a gradient of fire severity (unburnt through to canopy consumption) and surveyed at 3 and 10 years following fire. Owing to low detection rates for many species, analyses were limited to greater glider ( Petauroides volans ) occurrence and arboreal species richness. At both 3 and 10 years post‐fire, the greater glider was restricted to unburnt forest or sites affected only by understorey fire, which acted as fire refugia. Greater gliders were absent from sites affected by high severity, canopy‐consuming fires at both points in time. Greater glider occurrence was associated with high levels of canopy cover (>50%), which were typically those areas that were unburnt or burnt at low severity. The richness of arboreal mammals increased over time and was greater in unburnt or minimally affected forest. Our findings emphasize: (i) that fire severity is an important driver of the distribution of arboreal mammals; and (ii) the importance of recognizing longer‐term effects of fire severity in assessing species distributions, even in highly resilient forest communities. Recent advances in mapping fire severity provide new opportunities to assess the effects of fire severity on the distributional patterns of fauna in eucalypt forests.